Unexplained Aspects of Anemia of Inflammation - Elizabeth A. Price; Stanley L. Schrier (Advances in Hematology)
Anemia of inflammation (AI), also known as anemia of chronic inflammation or anemia of chronic disease was described over 50 years ago as anemia in association with clinically overt inflammatory disease, and the findings of low plasma iron, decreased bone marrow sideroblasts and increased reticuloendothelial iron. Pathogenic features underlying AI include a mild shortening of red cell survival, impaired erythropoietin production, blunted responsiveness of the marrow to erythropoietin, and impaired iron metabolism mediated by inflammatory cytokines and the iron regulatory peptide, hepcidin. Despite marked recent advances in understanding AI, gaps remain, including understanding of the pathogenesis of AI associated with “noninflammatory” or mildly inflammatory diseases, the challenge of excluding iron deficiency anemia in the context of concomitant inflammation, and understanding more precisely the contributory role of hepcidin in the development of AI in human inflammatory diseases.